181k views
0 votes
What times what equal -7 but adds up to equal -2

1 Answer

3 votes

Answer:

a*b=(-7)

a+b=(-2)

Represent a with b -> a=(-2)-b

Instead of a write (-2-b) in the first equation -> b*(-2-b)=-b^2-2b=7

b^2+2b-7=0

Solving this b=-1-2√2 and b=-1+2√2

Since a was equal -2-b we have these two solutions (a=(-1+2√2);b=(-1-2√2)) and (a=(-1-2√2);b=(-1+2√2))

Because the answers we got are the same only replaced we that numbers are (-1+2√2);(-1-2√2)). But write both answers to avoid any mistakes/misunderstanding.

User Morktron
by
5.7k points